The Poetry of the Pandemic - Burrow, Lauren E.; Jeffery, Tonya D. (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
This autoethnographic essay is a co-constructed endeavour that documents how we—a MotherScholar and a Black Woman scholar—both used poetic inquiry as feminist methodology (Faulkner) in order to respond to and find reprieve from the emotional gamut we each experienced during COVID-19. Though not professional poets, we value the craft of poetry and found it most suitable to capture the emotional labour of performing our caregiving responsibilities as mother and grandmother in our respective home spaces while trying to maintain our (virtual) workloads in institutes of higher education. Poetry was an opportunity for us to make sense of our changing identities and unpredictable emotions while being constantly bombarded with experiences and roles we never asked for or ever anticipated confronting—at home or work. The poems vary in content and form in an attempt to capture the diversity of experiences we each encountered while attempting to weather the same storm but in different boats. Collectively, the poems speak to the competing messages of comfort and confusion we each received during this volatile and traumatic time. By sharing our lived experiences, we invite others to bear witness to our COVID-19 realities of being forced to care for everyone and everything while still trying to care for ourselves, and we hope that readers find solace in a shared story, adopt this selfinquiry method as a form of self-care, and/or are prompted to check on any and all of the mothers that are just trying to survive COVID-19. When home becomes your office When work invades your kitchen When you teach other people’s children while your own children sleep twenty feet away When online #crisisschooling is forcing you to choose between teaching your daughter math or being a good mom When the incessant, unmistakable ding of emails demanding accountability for your time, your whereabouts, your productivity bombards your screen— What are you doing?! Show me! Count it up. Tally it. Tally it again in a different format. Tally due today! New tally in a different format for a different reason due tomorrow!! Convince me you are doing your job!!! Your care for your children better not be getting in your way! —while you try to focus on the comforting hum of students learning from you online in another open tab When COVID-19 forces a nation to observe a stay-at-home order, when can a MotherScholar find her own space among the unsolicited, unreasonable, and unimaginable expectation to become all things, to all people, at all times When the pandemic tries to tell you that you CAN’T be a mother and a scholar in the same space, at the same time When?! Perhaps… …in the stolen moments between feeding children and contributing in Zoom meetings, …in the margins of a work journal borrowed from her children’s bag of returned school supplies, Perhaps … …in the form of a poem. (Burrow)